Evolution of the dipole polarizability in the stable tin isotope chain - Bassauer, S.; Von Neumann-Cosel, R.; Reinhard, Paul-Gerhard; Tamii, A.; Adachi, S.; Bertulani, C. A.; Chang, P. Y.; Colo, Gianluca; D'Alessio, A.; Fujioka, H.; Fujita, H.; Fujita, Y.; et al. (Physics Letters B, 2020)
The dipole polarizability of stable even-mass tin isotopes Sn-112,Sn-114,Sn-116,Sn-118,Sn-120,Sn-124 was extracted from inelastic proton scattering experiments at 295 MeV under very forward angles performed at RCNP. Predictions from energy density functionals cannot account for the present data and the polarizability of Pb-208 simultaneously. The evolution of the polarizabilities in neighboring isotopes indicates a kink at Sn-120 while all model results show a nearly linear increase with mass number after inclusion of pairing corrections. (C) 2020 The Authors. Published by Elsevier B.V.
CRIS-Team WoS Importer:2020-11-13